Predictive Factors for Radiological Outcomes following Surgical Treatment of Acetabulum Fractures - Singjam, MD, Udomsin (Journal of Southeast Asian Orthopaedics, 2022)
Objective: The purpose of this study was to evaluate the effects of various factors on radiological outcomes following surgical treatment of displaced acetabular fractures. Materials and Methods: Radiological outcomes of 81 acetabular fractures which had been surgically treated from October 2014 to September 2017 were evaluated. Factors in the analysis included age, gender, mechanism of injury, smoking, pattern of fractures, time before surgery, initial displacement, and quality of reduction. Multivariate logistic regression analysis was performed to calculate predictive factors. Results: Of the 81 acetabular fractures, 57 (70.37%) were males and 24 (29.63%) were females. The mean age was 38.67 years (range 15-68). The mechanism of injury in 65 (80.25%) of the cases was a traffic vehicle accident and in 16 (19.75%) it was a fall from height. Of the patients, 25 (31.86%) smoked. Fracture types included simple fractures 30 (30.07%) and associated fractures 51 (62.96%). The mean time to surgery was 15.07 days (range 1-59). There was an associated hip dislocation in 27 cases (33.33%), initial fracture displacement ≤ 20 mm in 61 cases (75.31%) and displacement > 20 mm in 20 cases (24.69%). Of the fracture reductions, 20 (20.49%) were anatomical reductions, 26 (32.20%) were categorized as good reductions and 35 (43.21%) were rated as poor reductions. Radiological outcomes were good in 35 cases (43.21%), fair in 23 cases (28.40%) and poor in 23 cases (28.40%). None of the cases had an excellent outcome. Age, gender, mechanism of injury, and time to surgery were not correlated with radiological outcomes. Variables that were statistically significantly associated with outcomes were quality of reduction (p=0.000), initial displacement (p=0.007), fracture pattern (p=0.021) and associated hip dislocation (p=0.030). Conclusions: Poor reduction, initial displacement ≥ 20 mm, associated hip dislocation, and fracture pattern are correlated with a poor outcome prognosis for surgically treated acetabular fractures.